2004
DOI: 10.1074/jbc.m305369200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor STRA13 Regulates a Subset of Peripheral Circadian Outputs

Abstract: Central and peripheral mammalian circadian clocks regulate a variety of behavioral and physiological processes through the rhythmic transcription of hundreds of clock-controlled genes. The circadian expression of many transcriptional regulators suggests that a major part of this circadian gene network is indirectly regulated by clock genes. Here we show that the basic helixloop-helix transcriptional repressor Stra13 is rhythmically expressed in mouse peripheral organs. The circadian transcription of Stra13 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
68
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 50 publications
6
68
0
1
Order By: Relevance
“…Stra13 (Dec1) encodes a circadian-controlled transcriptional repressor/regulator of multiple genes, including several downstream circadian genes (35). Stra13 transcription is activated by CLOCK:BMAL1, whereas the STRA13 protein acts as a repressor of CLOCK:BMAL1 activity (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stra13 (Dec1) encodes a circadian-controlled transcriptional repressor/regulator of multiple genes, including several downstream circadian genes (35). Stra13 transcription is activated by CLOCK:BMAL1, whereas the STRA13 protein acts as a repressor of CLOCK:BMAL1 activity (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Stra13 transcription is activated by CLOCK:BMAL1, whereas the STRA13 protein acts as a repressor of CLOCK:BMAL1 activity (35,36). Maximal levels of Stra13 mRNA in liver have been reported to coincide with the peak of CLOCK: BMAL1 transcriptional activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work investigating the respective contributions of feeding and of the circadian clock to hepatic rhythmic gene expression using clock-deficient mice and the temporally restricted feeding paradigm has shown that oscillations of food-induced transcripts, including those from the gluconeogenic and fatty acid oxidation pathways, are modulated and consolidated by the clock. 37 Reciprocally, the robustness of the clock and its immediate downstream targets is increased by temporally restricted feeding. The expression of BAF60a itself is not altered by food signals, 24 but it is a clock target that modulates the expression of food-driven metabolic genes, such as PEPCK and Cpt1a.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins include the helix-loop-helix transcription factors, such as Differentially Expressed in Chondorocytes-1 and -2 (DEC1 and DEC2) and Inhibitor of DNA Binding 2 (ID2). These proteins can inhibit CLOCK⅐BMAL1 activities possibly by interfering with formation of the CLOCK⅐BMAL1 complex (27)(28)(29). DEC1 protein was also reported to delay the phases of Per1, Dbp, and Nr1d1 in cells after serum synchronization (30).…”
Section: Discussionmentioning
confidence: 99%